2016
DOI: 10.1007/s00360-016-0975-3
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-induced thermogenesis is up-regulated by the first cold-water immersions in juvenile penguins

Abstract: The passage from shore to marine life is a critical step in the development of juvenile penguins and is characterized by a fuel selection towards lipid oxidation concomitant to an enhancement of lipid-induced thermogenesis. However, mechanisms of such thermogenic improvement at fledging remain undefined. We used two different groups of pre-fledging king penguins (Aptenodytes patagonicus) to investigate the specific contribution of cold exposure during water immersion to lipid metabolism. Terrestrial penguins t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
1
9
1
Order By: Relevance
“…Thus, both groups exhibited the same thermal sensitivity to cold water, increasing their metabolic heat production when exposed to the same lower critical water temperature of 26-27°C or less. Such high temperatures of the lower limit of the thermoneutral zone in water have previously been reported in several penguin species (Kooyman et al, 1976;Barré and Roussel, 1986;Dumonteil et al, 1994;Teulier et al, 2016). These results clearly indicate that at the time of their first departure out to sea, juveniles are already equipped to be effective endotherms in cold water.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Thus, both groups exhibited the same thermal sensitivity to cold water, increasing their metabolic heat production when exposed to the same lower critical water temperature of 26-27°C or less. Such high temperatures of the lower limit of the thermoneutral zone in water have previously been reported in several penguin species (Kooyman et al, 1976;Barré and Roussel, 1986;Dumonteil et al, 1994;Teulier et al, 2016). These results clearly indicate that at the time of their first departure out to sea, juveniles are already equipped to be effective endotherms in cold water.…”
Section: Discussionsupporting
confidence: 74%
“…This is supported by the fact that (i) cold-deacclimatized juveniles, i.e. juveniles kept for 2 weeks at 20°C, are less efficient thermoregulators during cold immersion than sea-acclimatized penguins (Barré and Roussel, 1986); and (ii) 10 successive immersions in cold water can improve the thermoregulatory capacity of cold-deacclimatized juveniles (Barré and Roussel, 1986) but not of juveniles kept outside in their natural environment (Teulier et al, 2016), which in turn exhibit the same thermoregulatory capacity as sea-acclimatized immatures ( present study). Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). Previous studies showed that the thermogenic capacity of juvenile king penguins increases after repeated experimental submersion in cold water (Barré and Roussel, 1986;Talbot et al, 2004;Teulier et al, 2016) and is considerably higher in immature birds (after ∼1 year at sea) than in juveniles before their first departure to sea (Teulier et al, 2012). Hence, the relatively high peripheral temperatures during diving that we observed in juveniles during their initial period at sea could potentially also be a consequence of insufficient thermogenic capacity, so that birds avoid a deeper temperature drop by maintaining some peripheral perfusion.…”
Section: Seasonal Changes In Body Condition and Insulation Statusmentioning
confidence: 99%
“…2004; Teulier et al . 2016). In both cases, increases in flux through pathways of mitochondrial energy metabolism – either to support ATP synthesis or to counteract proton leak – is an important source of heat production.…”
Section: Introductionmentioning
confidence: 99%